1990
DOI: 10.1128/jcm.28.7.1519-1524.1990
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the ATB 32 A system for identification of anaerobic bacteria isolated from clinical specimens

Abstract: A new miniaturized 4-h method for the identification of anaerobic bacteria, ATB 32 A (API System SA, Montalieu Vercieu, France), was evaluated against conventional methods of identification. The evaluation was done by using 260 recent clinical isolates and 21 reference strains of anaerobic bacteria. All reference strains were correctly identified and did not figure in the detailed analysis. Of the 140 gram-negative bacilli, 90.6% of Bacteroides spp. and 95.5% of Fusobacterium spp. were correctly identified to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Although these systems have written descriptions of the colors of positive and negative tests, interpretation of the results of these tests is not always clear (8). In each of the three identification systems that we tested, some of the results of the reactions were difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%
“…Although these systems have written descriptions of the colors of positive and negative tests, interpretation of the results of these tests is not always clear (8). In each of the three identification systems that we tested, some of the results of the reactions were difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with the data cited from the literature (11, 13, 15, 16), they most closely resembled P. oris or P. buccae, but these two species could not be further distinguished by common phenotypic tests. Then, an enzyme activity assay system was employed (14). As shown in Table 2 the isolates showed a very similar pattern in 29 tests, especially both /3 -N-acetylglucosaminidase and a-fucosidase activities (17), to a type strain JCM 8540T of P. oris.…”
Section: Identification Of Isolated Strainsmentioning
confidence: 98%
“…Marler et al (174) identified only 90 of 126 strains (72%) of GPAC to the species level; 37% of the strains of P. anaerobius were misidentified, but the incorrect tests were not detailed. Three of the four more recent evaluations (153,169,192,203) of the ATB 32A kit (now renamed Rapid ID 32 A) have reported favorably. In the largest study (192), which included a comprehensive collection of type and reference strains, Murdoch and Mitchelmore were able to place 246 of 256 clinical strains (96%) in 1 of 10 PEP groups.…”
Section: Downloaded Frommentioning
confidence: 99%